Smoking, genetic predisposition, and colorectal cancer risk - Chen, Xuechen; Jansen, Lina; Guo, Feng; Hoffmeister, Michael; Chang-Claude, Jenny; Brenner, Hermann (Clinical and translational gastroenterology, 2021)
INTRODUCTION: - Smoking and genetic predisposition are established risk factors for colorectal cancer (CRC). We aimed to assess and compare their individual and joint impact on CRC risk using the novel approach of genetic risk equivalent (GRE). - METHODS: - Data were extracted from the Darmkrebs: Chancen der Verhütung durch Screening study, a large population-based case-control study in Germany. A polygenic risk score (PRS) based on 140 CRC-related single nucleotide polymorphisms was derived to quantify genetic risk. Multiple logistic regression was used to estimate the individual and joint impact of smoking and PRS on CRC risk, and to quantify the smoking effect in terms of GRE, the corresponding effect conveyed by a defined difference in PRS percentiles. - RESULTS: - There were 5,086 patients with CRC and 4,120 controls included. Current smokers had a 48% higher risk of CRC than never smokers (adjusted odds ratio 1.48, 95% confidence interval 1.27-1.72). A PRS above the 90th percentile was significantly associated with a 3.6-, 4.3-, and 6.4-fold increased risk of CRC in never, former, and current smokers, respectively, when compared with a PRS below the 10th percentile in never smokers. The interaction between smoking and PRS on CRC risk did not reach statistical significance (P = 0.53). The effect of smoking was equivalent to the effect of having a 30 percentile higher level of PRS (GRE 30, 95% confidence interval 18-42). - DISCUSSION: - Both smoking and the PRS carry essentially independent CRC risk information, and their joint consideration provides powerful risk stratification. Abstinence from smoking can compensate for a substantial proportion of genetically determined CRC risk.